Process Diary as Methodological Approach in Longitudinal Phenomenological Research - Woll, Heidi (The Indo-Pacific journal of phenomenology, 2013)
This article focuses on the process diary as a qualitative instrument in phenomenological research. The first part of the article provides a brief historical review on the use of diaries in social and health research. The second part of the article presents an example of how the process diary may be used based on the profile of a participant in the study "Aging with Cerebral Palsy". The third part of the article deals with the challenges of analyzing the data provided by process diaries and discusses the strengths and weaknesses of this method. The article concludes with a brief discussion concerning the kinds of situations where the process diary is a suitable research instrument. This section of the article also touches upon the ethical challenges involved in using the process diary in longitudinal phenomenological research.